Ingen spøk En studie av religion og humor - Botvar, Pål Ketil (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2019)
"How do Norwegians feel about religious humour? What do comedians take into consideration when producing and performing jokes about religion? How is humour about religion presented in television comedies, film comedies and men's magazines? How do different religious groups relate to humour about their own faith? The relationship between religion and humour can be contentious - religion is not always something to make light of - and yet, religion and humour are in dialogue, negotiating ways to accommodate each other. There is also much humour to be found in religious milieus. This anthology addresses encounters between humour and religion in a variety of contexts. The book consists of contributions written by people from different disciplines with expertise in religion, media and humour. Practitioners are represented through interviews with stand-up comedians. The book is aimed at everyone interested in the role of religion in humoristic settings, as well as professionals in the fields of media and religion, politicians and other decision-makers, and students in social sciences, religious studies and media studies."